Kemampuan Pemahaman Konsep Matematis Siswa Sekolah Menengah Pertama pada Persamaan Garis Lurus Ditinjau dari Self-Regulated Learning - Faisal Faisal; Sumarni Sumarni; Mohamad Riyadi (ARITHMETIC: Academic Journal of Math, 2023)
Students' Self-Regulated Learning (SRL) has an influence on students' understanding of mathematical concepts. The purpose of this study was to analyze the SRL and the ability to understand students' mathematical concepts in terms of SRL. This research is included in the type of descriptive qualitative. The data collection techniques used were SRL questionnaires, tests of understanding mathematical concepts, interviews, and observations. The subjects were 22 students in grade 8A SMPN 5 Kuningan, and took 6 samples using a purposive technique of two students from each SRL category (high, medium, low). Data analysis includes data reduction, data presentation, conclusion drawing, and method triangulation. Based on 22 students who filled out the SRL questionnaire, 4 were in the low category, 14 were in the medium category, and 4 were in the high category. While the results of understanding mathematical concepts, 7 categories are low, 13 categories are moderate, and 2 categories are high. Based on the 6 selected subjects, low category subjects were able to fulfill 2-3 indicators of ability to understand mathematical concepts although not perfect, medium category subjects were able to fulfill 5-7 indicators although not perfect, and high category subjects were able to fulfill 6-8 indicators almost perfectly.